Deleting IGF-1 receptor from forebrain neurons confers neuroprotection during stroke and upregulates endocrine somatotropin - C. Daniel De Magalhaes Filho; Laurent Kappeler; Joëlle Dupont; Julien Solinc; Sonia Villapol; Cécile Denis; Marika Nosten‐Bertrand; Jean‐Marie Billard; Annick Blaise; François Tronche; Bruno Giros; Christiane Charriaut‐Marlangue; et al. (2016)
Insulin-like growth factors control numerous processes, namely somatic growth, metabolism and stress resistance, connecting this pathway to aging and age-related diseases. Insulin-like growth factor signaling also impacts on neurogenesis, neuronal survival and structural plasticity. Recent reports demonstrated that diminished insulin-like growth factor signaling confers increased stress resistance in brain and other tissues. To better understand the role of neuronal insulin-like growth factor signaling in neuroprotection, we inactivated insulin-like growth factor type-1-receptor in forebrain neurons using conditional Cre-LoxP-mediated gene targeting. We found that brain structure and function, including memory performance, were preserved in insulin-like growth factor receptor mutants, and that certain characteristics improved, notably synaptic transmission in hippocampal neurons. To reveal stress-related roles of insulin-like growth factor signaling, we challenged the brain using a stroke-like insult. Importantly, when charged with hypoxia-ischemia, mutant brains were broadly protected from cell damage, neuroinflammation and cerebral edema. We also found that in mice with insulin-like growth factor receptor knockout specifically in forebrain neurons, a substantial systemic upregulation of growth hormone and insulin-like growth factor-I occurred, which was associated with significant somatic overgrowth. Collectively, we found strong evidence that blocking neuronal insulin-like growth factor signaling increases peripheral somatotropic tone and simultaneously protects the brain against hypoxic-ischemic injury, findings that may contribute to developing new therapeutic concepts preventing the disabling consequences of stroke.